Dofetilide‐Induced Long QT and Torsades de Pointes - Aktas, Mehmet K. (Ann Noninvasive Electrocardiol, 2007)
Dofetilide, a new class III antiarrhythmic agent, has been approved as an antiarrhythmic agent for the treatment of atrial fibrillation and atrial flutter. Dofetilide selectively inhibits the rapid component of the delayed rectifier potassium current resulting in a prolongation of the effective refractory period. Like other drugs that affect potassium currents, the prolonged QT interval occurring in the patients treated with dofetilide can be complicated by torsades de pointes. We report four cases of dofetilide‐induced QT prolongation and torsades de pointes. We discuss the risk factors for the development of dofetilide‐induced long QT and torsades de pointes and review the current literature.